Association between triglyceride-glucose index and heart failure in patients with type 2 diabetes mellitus: a cross-sectional study - Yan, Tong; Lv, Xiaoxia; Chen, Jing (Frontiers in Cardiovascular Medicine, 2026)
ObjectiveThis study aimed to investigate the association between the triglyceride-glucose (TyG) index and heart failure (HF) in patients with type 2 diabetes mellitus (T2DM).MethodsThis single-center cross-sectional study enrolled 848 hospitalized T2DM patients aged ≥50 years at Xi'an Gaoxin Hospital between January 1, 2024, and January 1, 2025. The TyG index was calculated for each patient, and participants were stratified into three tertiles (T1, T2, T3) based on TyG levels. HF was diagnosed in accordance with the 2021 guidelines of the European Society of Cardiology (ESC). Univariate logistic regression was first used to identify variables significantly associated with HF (P < 0.05), which were then included in multivariate logistic regression analyses to examine the independent association between TyG and HF risk. Subgroup analyses were also conducted to examine whether the association between TyG and HF varied by age, sex, smoking status, hypertension, and body mass index (BMI). To evaluate the predictive value of the TyG index for HF, receiver operating characteristic (ROC) curves were plotted, and the area under the curve (AUC) was calculated.ResultsAmong the 848 participants, 242 (28.5%) had HF. Higher TyG levels were independently associated with increased HF risk. In the fully adjusted model, the second (T2: OR = 1.655, P = 0.026) and third tertiles (T3: OR = 1.762, P = 0.018) were significantly associated with elevated odds of HF compared to the lowest tertile (T1). The TyG index as a continuous variable also showed a robust association (OR = 1.493, P = 0.002). Subgroup analyses revealed particularly strong associations in individuals aged ≥70 years, males, non-smokers, hypertensive patients, and those with body mass index <24 kg/m2. ROC analysis indicated that the TyG index not only showed modest discriminative ability for HF but also enhanced the predictive performance of a baseline model consisting of conventional variables (P < 0.05).ConclusionElevated TyG index is independently associated with increased risk of HF in patients with T2DM. It may serve as a clinically accessible, cost-effective biomarker for early HF risk identification, particularly in high-risk subpopulations.